Pressing the Subject: Critical Theory and the Death Drive - McIvor, David W. (Constellations (Oxford, England), 2015)
Critical theory is still in the midst of what Axel Honneth has termed a "far-reaching crisis," a crisis that touches on both its conception of the autonomous subject and the political visions sketched on the basis of this conception. This paper argues that this crisis within critical theory stems in part from Habermas' early engagements with--and eventual retreat from--psychoanalysis.